1981
DOI: 10.1126/science.7025208
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cells: Their Roles in Defenses Against Disease

Abstract: Natural killer cells are a recently discovered subpopulation of lymphoid cells that are present in most normal individuals of a range of mammalian and avian species. Natural killer cells have spontaneous cytolytic activity against a variety of tumor cells and some normal cells, and their reactivity can be rapidly augmented by interferon. They have characteristics distinct from other types of lymphoid cells and are closely associated with large granular lymphocytes, which comprise about 5 percent of blood or sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
442
3
6

Year Published

1987
1987
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,298 publications
(463 citation statements)
references
References 86 publications
11
442
3
6
Order By: Relevance
“…Furthermore, a similar target spectrum (lysis of Daudi but not the stimulator LCL) and the same productive Vy/S gene expression (assessed by mAb BB3 and TiyA) was independently detected in all TCRy/S-1 + , STCSI -clones derived from four different donors in Rotterdam . The results presented here strongly suggest that human BB3/TiyA + T cells recognize different determinants than non-MHC-restricted NK cells (3,4) or IL-2-activated MHC-restricted a/o T cells (31). The relationship of these target structures to known antigens for y/S T cells remains to be determined (12)(13)(14)32).…”
Section: Resultsmentioning
confidence: 92%
“…Furthermore, a similar target spectrum (lysis of Daudi but not the stimulator LCL) and the same productive Vy/S gene expression (assessed by mAb BB3 and TiyA) was independently detected in all TCRy/S-1 + , STCSI -clones derived from four different donors in Rotterdam . The results presented here strongly suggest that human BB3/TiyA + T cells recognize different determinants than non-MHC-restricted NK cells (3,4) or IL-2-activated MHC-restricted a/o T cells (31). The relationship of these target structures to known antigens for y/S T cells remains to be determined (12)(13)(14)32).…”
Section: Resultsmentioning
confidence: 92%
“…21,37 Although the association between impaired NCA and the development of breast cancer has not been established, research on humans and other species points to a significant role of NCA in preventing the development of cancer, including breast cancer, and its metastases. [1][2][3][4]8,9 Additional studies doc- norepinephrine levels and state anxiety, (d) IL-2-induced NCA and emotion-focused coping, (e) IL-2-induced NCA and problem-focused coping, (f) IL-2-induced NCA and perceived control, (g) norepinephrine levels vs. perceived control, (h) IL-2 secretion and perceived control, (i) norepinephrine levels and IL-2-induced NCA and (j) epinephrine levels and IL-2 secretion. In general, correlations are done with data from both DBCP and controls, whereas correlations with perceived control (f-h) are done for DBCP only.…”
Section: Discussionmentioning
confidence: 99%
“…Various in vivo studies in humans and mice have shown the significant role of different natural cytotoxic lymphocyte populations in preventing the development of cancer or its metastases. [1][2][3][4] However, only a few studies have investigated NCA of peripheral blood lymphocytes among healthy individuals in a general population or those at increased risk of developing cancer. [5][6][7] NCA has also been demonstrated to be an independent prognostic marker in patients with cancer.…”
mentioning
confidence: 99%
“…NK cells, which are distinguished from Tc cells by expression of Fcg receptor III (CD16), CD56 as well as by the lack of a rearranged TCR [1], are able to kill certain tumor cells in an apparently non-MHC restricted manner without need for prior sensitization [2,3]. Thereby, the NK cells do not recognize presented antigens, and their cytotoxicity occurs more early than Tc cells.…”
Section: Introductionmentioning
confidence: 99%